2023
DOI: 10.1088/1475-7516/2023/06/001
|View full text |Cite
|
Sign up to set email alerts
|

Polarized gravitational waves in the parity violating scalar-nonmetricity theory

Abstract: There has been increasing interest in investigating the possible parity violating features in the gravity theory and on the cosmological scales. In this work, we consider a class of scalar-nonmetricity theory, of which the Lagrangian is polynomial built of the nonmetricity tensor and a scalar field. The nonmetricity tensor is coupled with the scalar field through its first order derivative. Besides the monomials that are quadratic order in the nonmetricity tensor, we also construct monomials that are cubic ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 133 publications
0
1
0
Order By: Relevance
“…Other recent studies on PV gravities can be found in refs. [23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Jhep08(2023)070mentioning
confidence: 99%
“…Other recent studies on PV gravities can be found in refs. [23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Jhep08(2023)070mentioning
confidence: 99%